La gestión por procesos como herramienta fundamental en el aseguramiento de la calidad de las carreras universitarias - Soto-Grant, Andrea (Universidad de Costa Rica, 2022)
This essay raises the need to incorporate management tools to ensure the quality of university careers as an important part of an effective educational administration. It is based on the premise that, although all academic programs manage to complete the different quality assurance activities, this management can become complex and confusing for all the people involved because the tasks are carried out in different ways. Due to the above, it is necessary to incorporate institutional procedures so that the people involved can follow a specific route, elaborated from the experience of the executors, and adapted to the needs of each institution and specific career. The foregoing would allow achieving quality assurance in a more efficient and effective way in times when the optimal use of resources becomes transcendental in the execution of the substantive tasks of the universities and the achievement of the proposed objectives. For this analysis, a hermeneutical-dialectical approach was adopted, since what is sought is to understand the phenomenon of the quality of university careers from the particularity and the specific context of the sector, of each institution and of each specific career. Therefore, this approach allows considering the conditions for each case.